PENGARUH FAKTOR-FAKTOR BRAND EQUITY TERHADAP BRAND TRUST PRODUK AMDK MEREK AQUA (STUDI PADA PELANGGAN DI KABUPATEN LOMBOK TIMUR). - Bambang Triaji (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
The aims of this reasearch are to know how the dimesions of brand equity which consists of brand awareness, brand associations, perceived quality and brand loyalty have partially and simultaneously influences with brand trust for AQUA mineral water customer’s in Kabupaten Lombok Timur. Data collections was carried out with interviews and questionnaires and sampling method in this research use non probabilty sampling-purpose sampling methods. The number of samples are 95 customers who always buy AQUA mineral water in Kabupaten Lombok Timur. Data analysis was performed using simple linear regression and multiple linear regression. The results in this research shows that the dimensions of brand equity (brand awareness, brand associations, perceived quality and brand loyalty) partially and simultaneously have some significant influences with brand trust. Keywords : Brand equity, Brand awareness, Brand associations, Perceived quality, Brand loyalty, Brand trust.